Aerosol physico–optical–radiative characterization and classification during summer over Ny-Ålesund, Arctic. Issue 22 (17th November 2021) - Sonbawne, Sunil Manohar; Devara, Panuganti C. S.; Bhawar, Rohini; P. R. C., Rahul; Siingh, Devendraa; Fadnavis, Suvarna; Panicker, Abhilash. S.; Pandithurai, Govindan
ABSTRACT: With an aim to study the year-to-year changes in physical, optical, and radiative properties of polar aerosols, special observation campaigns were conducted during three consecutive summers of 2010, 2011 and 2012 over Ny-Ålesund (78.9°N, 11.9°E, 42 m AMSL), Arctic, employing a ground-based Multi-channel Solar-radiometer (MICROTOPS II Sun- photometer). In the present study, the columnar Aerosol Optical Depth (AOD) at λ = 500 nm and the Angstrom exponent (α) data sets are used to analyse the daily mean AOD and α by using a liner regression (best-fit) method. The results highlight that the columnar aerosol optical depth (mean AOD@500 nm for the study period) is 0.144 ± 0.05. Signature of secondary aerosol formation through marine sources based on variation in two wavelength AODs is also studied. These columnar AOD measurements over the study region are found to be in good agreement within experimental limitations with the synchronous MODIS satellite derived values. The 3 years' α mean value is found to be 0.797 ± 0.328 within the range of 0.01–1.4. The frequency of occurrence and relative frequency histograms of α exhibited two modes centred at around 1.2 and 0.8. The primary and secondary modes reveal that the marine aerosols in the study region are mixed type, and they contribute about 44%, with the accumulation particles alone contributing about 31%. We found a close correspondence between aerosol optical properties and local meteorological conditions over the experimental location. The aerosol radiative forcing estimations revealed higher negative aerosol radiative forcing (indicating cooling) at Bottom-of-the-Atmosphere (BOA) and positive radiative forcing (indicating warming) in the Atmosphere (ATM) and Top-of-the-Atmosphere (TOA) during 2012 as compared to those obtained during 2010 and 2011, which is consistent with the observed AOD and α. The airmass back-trajectory model analysis also showed intrusion of anthropogenic aerosols from neighbouring regions into the study region, particularly during the year 2012.